2022
DOI: 10.1177/10556656221080359
|View full text |Cite
|
Sign up to set email alerts
|

Cone-Beam Computed Tomographic Assessment of Maxillary Sinus Characteristics in Patients With Cleft Lip and Palate: A Systematic Review and Meta-Analysis

Abstract: The aim of this systematic review and meta-analysis was to evaluate the maxillary sinus characteristics of patients with cleft lip and palate (CLP). The study included manuscripts which met the following criteria: (1) study of individuals with CLP in any age group or gender and (2) study of individuals in whom assessment of maxillary sinus characteristics had been done by cone-beam computed tomography. Studies with (1) individuals having special health-care needs and (2) individuals with any syndrome affectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
0
7
0
1
Order By: Relevance
“…These steps resulted in the inclusion of 18 more SRs. Altogether, 144 SRs and MAs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , ...…”
Section: Resultsunclassified
See 4 more Smart Citations
“…These steps resulted in the inclusion of 18 more SRs. Altogether, 144 SRs and MAs [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , ...…”
Section: Resultsunclassified
“…It was observed that only three studies performed before 2010 could qualify during the two-stage scrutiny [ 72 , 112 , 113 ]. Among the journals, the highest number of papers (n = 30) was published in the Cleft Palate Craniofacial Journal (CPCJ) [ 21 , 35 , 46 , 47 , 48 , 49 , 63 , 65 , 66 , 76 , 86 , 92 , 94 , 100 , 101 , 115 , 116 , 121 , 123 , 125 , 128 , 137 , 140 , 142 , 146 , 150 , 152 , 155 , 161 , 162 ] followed by The Cochrane Library (n = 8) [ 9 , 16 , 68 , 88 , 92 , 93 , 100 , 106 ] and the International Journal of Oral and Maxillofacial Surgery (n = 7) [ 31 , 72 , 89 , 93 , 106 , 110 , 135 ]. There was diversity among the journals of different specialties that had published the SRs related to CLP ( Supplementary Material S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations